FORMATION OF NET RATE IN ADDITIONAL PENSION INSURANCE, FACTORS AFFECTING LIFE EXPANSION - Hamroeva Dilsuz Yakhyoevna (International Journal of Innovations in Engineering Research and Technology, 2022)
In this work, protection from accidents that cannot be predicted in advance based on the planning of insurance activities, reduction of the damages of these events, the role of life insurance in the insurance market, the factors affecting it and, in turn, the dependence of these factors on life expectancy, the insured's annuity in the insurance pension program, reaching a certain age the insurance premiums to be paid by him have been studied.